• :00Days
• :00Hours
• :00Mins
• 00Seconds
A new era for learning is coming soon

Suggested languages for you:

Americas

Europe

Q3.

Expert-verified
Found in: Page 400

### Pre-algebra

Book edition Common Core Edition
Author(s) Ron Larson, Laurie Boswell, Timothy D. Kanold, Lee Stiff
Pages 183 pages
ISBN 9780547587776

# Solve the equation Check your solution. $4\left(7-2t\right)=4$

The solution of our given equation would be $t=3$.

See the step by step solution

## Step 1. Given Information.

An equation: $4\left(7-2t\right)=4$

## Step 2. Calculation.

To solve our given equation, we use opposite operations as shown below:

$\begin{array}{c}4\left(7-2t\right)=4\left(\text{Given equation}\right)\\ \frac{4\left(7-2t\right)}{4}=\frac{4}{4}\left(\text{Dividing both sides by 4}\right)\\ 7-2t=1\\ 7-7-2t=1-7\left(\text{Subtracting 7 from both sides}\right)\\ -2t=-6\\ \frac{-2t}{-2}=\frac{-6}{-2}\text{ }\left(\text{Dividing both sides by}-2\right)\\ t=3\end{array}$

Let us verify our answer by substituting $t=3$ in our original equation.

$\begin{array}{c}4\left(7-2t\right)=4\left(\text{Given equation}\right)\\ 4\left(7-2\left(3\right)\right)=4\text{ }\left(\text{Substituting}t=3\right)\\ 4\left(7-6\right)=4\\ 4\left(1\right)=4\\ 4=4\end{array}$

Since both sides of equation are equal, therefore, $t=3$ is a solution of our given equation.

## Step 3. Conclusion.

The solution of our given equation would be $t=3$.